Impact of the Chemical Elements Upon the Convective Flows in the Molten Metal of the Weld Pool; IOP Conference Series: Earth and Environmental Science; Vol. 66 : Ecology and safety in the technosphere - Sarychev V. D.; Chinakhov D. A. Dmitriy Anatol'evich; Solodsky S. A. Sergey Anatolievich; Granovskii А. Yu.; Nevskii S. А. (2017, 2017)
Title screen